BIMODAL INPUT IN TEACHING LISTENING COMPREHENSION EXERCISES - budiarto budiarto (Journal of English Language and Literature (JELL), 2016)
The objective of this study was to see whether bimodal input (audio and its tape-script) can increase students’ listening comprehension in TOEIC listening section. Three groups of freshmen were involved in this study. Before the experiment began, three groups took the same TOEIC listening pre-test. They were selected and put into three groups with roughly equal level based on pre-test scores. All of the three groups trained in the same listening comprehension skills and strategies, and after that they did the same TOEIC listening post-test. There were two experimental groups, one group was shown the tape-script during the listening exercises) and the other experimental group was provided tape-script in the post listening comprehension practices, while the control is not shown the tape-script at all. By using a projector, presentation slides of tape-script were shown to the two experimental groups, one group was exposed the tape-script and at the same time the students were reading the script, and the other group was exposed with the tape-script after they finished listening, in order to check and analyze some parts in the listening to make sure about they heard and to see the relevant information needed. The pre-test and post-test comparisons showed that all three groups performed better as indicated by the increase of the listening comprehension scores in the post test, so it may show that each group is eager to learn the language. Each has to deal with the test which consists of 100 questions broken down into four parts, photographs, questions and responses, conversations, and talks. The writer does not specify the results based on each part, but on basis of the whole listening section result instead.